The effects of alumina on the dense calcium phosphate synthesized from eggshell waste - Misran, Fatimah (2015)
Eggshell (ES) wastes were processed and used as starting materials for the synthesis of calcium phosphates (CaP) such as hydroxyapatite (HA) and tricalcium phosphates (TCP). Hydrothermal and mechanochemical synthesis methods were applied to synthesize hydroxyapatite and hydroxyapatite-alumina bioceramic composite powders with ultrafine microstructures from both eggshell wastes and chemical calcium precursors to develop bioceramics with enhanced mechanical properties for medical applications. Despite its attractive, bioactive and biocompatibile properties, CaP has been limited in applications due to the poor processability and mechanical strengths of the material. To further toughen the CaP matrix, nanocrystalline alumina (Al2O3) with the addition amounts of 15wt.% and 35wt.% was introduced. CaP in the form of dense compacts was prepared by uniaxial pressing and sintered through pressureless sintering method in air atmosphere at various sintering temperatures. The effects of the type of calcium sources, the synthesis pH conditions, the Al2O3 incorporation and the sintering temperature on the phase behaviour and the mechanical properties of the developed ceramic bodies were evaluated. The presence of HA and Al2O3 phase in the powder synthesis was confirmed through XRD, FT-IR and TGA analyses. However, the major phase detected in the developed dense compacts after sintering conducts was TCP. FESEM and EDX assessments showed nano-sized rods and spherical morphologies with corresponding element analysis of the synthesized powders. SEM analyses were used to observe the morphology and densification behaviour of the bioceramic compacts. Density, porosity, compression, elasticity, microhardness and fracture toughness tests were used to monitor the physical and mechanical properties. Statistical analysis using MINITAB was used to summarize the mechanical evaluations. The leading mechanical attributes were achieved by dense bioceramics synthesized from ES-based calcium precursor at pH 9 conditions after being sintered at 1250°C. Al2O3 reinforcements were preferred in small quantities to achieve better mechanical properties. The highest measurement of Vickers hardness and facture toughness was acquired through the sample that was synthesized at alkaline conditions, 15wt% alumina content and after being sintered at 1250°C with values of 4.76 GPa and 4.12 MPam1/2 respectively. Sintering temperature was concluded to be the most influencing variable parameter for every evaluation particularly for the enhancement of mechanical strength of the developed bioceramics.